INTEGRATED DISEASE MANAGEMENT OF BLIGHT OF PIGEONPEA CAUSED BY F. SP. PHYTOPHTHORA PHYTOPHTHORA DRECHSLERI CAJANI (Journal of Plant Disease Sciences, 2024)
Phytophthora Phytophthora drechsleri cajani blight of pigeonpea incited by f. sp. is one of the most destructive and wide spread disease. All the test fungicides, bioagents, botanicals and organic amendments integrated (pot culture, sick soil) for the management of f sp. were found to encourage Phytophthora drechsleri . cajani seed germination and reduce pre- and post-emergence mortalities in pigeonpea cv. BDN1. Of the treatments imposed, [Metalaxyl + Mancozeb] (SD @ 2g/lit water) + Mancozeb (ST @ 3 g / kg soil) + (ST @ 10 g/kg seed)+ Garlic (SD 50ml/kg T.harzianum soil) + Neem cake (SA @ 50 g/kg soil) treatment was found most effective with cent per cent seed germination (100.00%), significantly least average mortality (2.50%) and highest average mortality reduction (93.99%). This was followed by the treatments ., (Metalaxyl + Mancozeb), (Metalaxyl + Mancozeb) + Mancozeb and viz (Metalaxyl+Mancozeb) + Neem cake with seed germination each 85.00%, average mortality, respectively of 16.52, 16.18 and 16.18 per cent and average mortality reduction, respectively of 66.42, 67.25 and 67.25 per cent, Neem cake and (Metalaxyl + Mancozeb) + Garlic with seed germination each 80.00%, average mortality, respectively of 22.5 and 19.37 per cent and average mortality reduction, respectively of 53.26 and 59.51 percent.
Keywords: Pigeonpea; Phytophthora drechsleri; Fungicides; Bioagents; Botanicals; Mortality